Micronized carvedilol SR matrix tablet for improved dissolution - Chatterjee, Bappaditya (Lambert Academic Publishing, 2016)
Sustained release (SR) matrix formulation can overcome the disadvantages of frequent dosing of conventional tablet. Poor soluble drugs (BCS class II) suffer from low bioavailability due to low dissolution rate. Micronization is one of the easiest approaches to enhance solubility of drugs. Formulation of a SR matrix tablet with micronized drug particle will help to enhance dissolution as well as prolong the duration of drug release. In the research work entitled “micronized carvedilol SR matrix tablet for improved dissolution”, Carvedilol, a BCS class II β blocker drug is formulated as a SR matrix tablet with micronized drug particle. Direct compression method was applied to prepare tablet using PEO 301 as a release retardant polymer. The formulation was optimized by a 3 level factorial design considering amount of PEO 301 and hardness of tablet as dependent variables. In-vitro release study showed near about 100% of drug release in 12 hrs. for lowest particle size drug whereas for non-micronized drug it was less than 80%. The developed tablet showed desired stability for 3 months in accelerated conditions. The developed micronized carvedilol SR matrix tablet can be proposed for in-vivo assessment after relevant toxicity studies.